Pemenuhan Hak Mendapatkan Pelayanan Kesehatan Bagi Narapidana (Studi di Lembaga Permasyarakatan Kelas II A Curup) - Sandra Wijaya, Trio; Akbar Mulki Rahman, Malik (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Getting health services is a right for everyone, including someone who is serving a sentence of independence in a correctional facility. Prisoners who are serving a sentence of loss of independence with the same right to obtain health services provided by the state, so that there is no difference between other community members and prisoners. At this time, the author wants to see the extent to which health services are provided to inmates. Research conducted at the Class IIA Correctional Institution using qualitative methods with data techniques carried out by interviews and field observations. Data sobtained from primary data and secondary data. The provision of rights to health services in prisons has on average been given, seen from each correctional institution already has a health clinic that can provide health services to prisoners who are undergoing a criminal period, although there are some health games that cannot be given such as certain diseases. From the results of research conducted at the Class IIA Correctional Institution, Curup had 4 health workers consisting of 1 honorary doctor, 1 nurse and 2 midwives. With the condition that there are only 4 health workers and as many as 555 prisoners, of course, they cannot provide maximum health services. At the Curup Class IIA Correctional Institution health clinic there are 2 health services, namely general and special health services, for general health services it has been maximally provided but for special services health clinics collaborate with the health office for disease companions such as tuberculosis, HIV / AIDS, syphilis and other cooperation.